Financial Exclusion : A New Angle to Urban Poverty in Latin America - Solo, Tova M. (World Bank, Washington, DC, 2012)
Data gathered during studies conducted over the past four years in Mexico City, Mexico (Distrito Federal); Bogota, Colombia, and in several Brazilian cities suggests that in these countries somewhere between 65 and 85 percent of households are "unbanked", those who do not hold any kind of deposit or transaction account in any formal sector financial institution. This note addresses what can be done to bring banking to the unbanked - and vice versa using five cases from the region: 1) the Nicaragua Broad Based Access to Finance Project focuses on increasing the number of points of service to remote and unattended communities; 2) the Colombia Business Productivity and Efficiency Development Policy Loan also emphasizes increased service points through regulatory reform; 3) in Mexico, the National Savings and Financial Services Bank (BANSEFI for its acronym in Spanish) projects help to promote new service providers with state of the art technology and regulatory services; and 4) Brazil's government has developed alternative service payment systems and regulations to encourage access to savings.